Development of Higher Order Thinking Skills (HOTS) Assessment Instruments to Improve Students' Mathematical Creative Thinking Skills - Lili Nur Indah Sari; Irma Rizki Aulia E (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2022)
The purpose of learning in the millennial era is the development and improvement of students' high-level thinking skills. High-level abilities or often referred to as higher order thingking skills (HOTS) are the level of thinking of students with stages of analysis, evaluation and creation. The indicators of HOTS can be derived from the ability to think critically and think creatively. In order for students' mathematical HOTS abilities to be known, a HOTS assessment instrument is needed. The purpose of this study is the development of a mathematical HOTS assessment instrument for MTs class VII students. The type of research is a development adapted from the development of Borg and Gall. Analysis of research data using quantitative and quality analysis to determine the quality of the mathematical HOTS assessment instrument conducted a review based on the criteria of validity, reliability, difficulty index and differentiating power of the problem. The result of this development is that the HOTS assessment instrument with the form of a description of 15 questions and is suitable for use. The HOTS assessment instrument is included in a valid category that is based on expert assessment with an average score of 36.5 and an excellent category. The difficulty level of the question is moderate with an average difficulty index of 0.5 in the medium category and the differentiating power of the question is good with an average differentiating power index of 0.33 in the good category. The developed mathematical HOTS instrument also meets the reliable criteria with a reliability coefficient of 0.733.